Evolving Needs of Health Insurance Policyholders: Factors Shaping Decision-Making in the Post-Pandemic Era (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The COVID-19 pandemic has significantly transformed the whole scenario of choosing health insurance plans, making policyholders more alert and aware of health insurance policies and leading to heightened expectations from insurers in an era marked by increasing diseases. This highlights the importance of examining the influence of pandemic in the decision-making process of health insurance policyholders while selecting their policies. The present study therefore examines the novel factors influencing selection of policies by health insurance policyholders due to the lasting impact of pandemic. The study further analyses the role of these factors in addressing the evolving needs and priorities of policyholders that are emerging in the post-pandemic era. An empirical survey was conducted for this research on the health insurance policyholders from the state of Uttarakhand. The study utilises a sample of 232 respondents to examine key factors influencing policy selection and applied the Structural Equation Modeling (SEM) technique using SmartPLS SEM software to analyse the impact of the explored factors on the satisfaction level of policyholders. The results of the study reveal the pivotal role of comprehensive coverage, service accessibility, transparency, efficient claims processing, and affordability in shaping post-pandemic health insurance decisions. These factors provide valuable insights for insurers to design policies that align with the evolving needs and expectations of health insurance policyholders. The study suggests that insurers can enhance long-term growth and policyholder satisfaction by offering flexible, comprehensive plans, leveraging digital tools for better service delivery, and maintaining transparency in communication. Furthermore, adopting personalised strategies and value-added services will foster trust and strengthen customer relationships in the post-pandemic environment.